Epidemiology and seropositivity of dengue fever cases in a tertiary care hospital of NCR in 2013 - Gupta, Shilpi; Bansal, Sachin (Eastern Journal of Medical Sciences, 2017)
Background: Dengue has been known to be endemic in India for over two centuries. Dengue fever is more commonly seen in adultsand older children. Clinical presentation varies from mild to severe fatal forms; therefore, laboratory diagnosis is very essential.Objective: The surveillance study was conducted to analyze dengue seropositivity and epidemiological profile among patients withdengue fever like illness who presented to the outpatient department or was admitted to a tertiary care private hospital in Ghaziabad,Uttar Pradesh from January 2013 to December 2013. Materials and Methods: Serum samples from 1186 clinically suspecteddengue fever cases (671 males and 515 females) were received in serology laboratory over the period of 1 year. The samples werescreened for non-structural protein 1 (NS1) antigen and IgM and IgG dengue specific antibodies by rapid immunochromatographictest. Results: Out of total 1186 blood samples tested, 574 were found to be positive for dengue infection. Of 574 blood samples, NS1Ag was positive in 498 (86.7%) cases while IgM with or without NS1 Ag was positive in 15 (2.6%) cases. Conclusion: A detailedand continuous epidemiological surveillance is required for monitoring the incursions and spread of dengue viruses. This will helpin undertaking and implementing effective control and management strategies.